STUDI EKSPERIMENTAL PENGARUH ABU SEKAM PADI SEBAGAI BAHAN TAMBAH PADA PAVING BLOCK TERHADAP KUAT TEKAN, DAYA SERAP AIR, DAN KETAHANAN GUNCANGAN - Magribi, Amal Ichlasul; Fitnul, La Ode Muhamad; Bahar, Adwan; Natsir, Rahmat; Safridin, Safrudin (Civil Engineering Scientific Journal, 2025)
AbstractBased on SNI 03-0691-1996, paving block is a building material composition made from the mixture of Portland cement or similar hydraulic adhesives, water and aggregate with or without other additional material that will reduce the concrete quality. The burned rice husk ash will be used in this research. It aims to produce strong, environmental friendly and economical paving block. With the use of rice husk ash percentages as cement substitution are 5%, 10%, 15%, and 20%. The paving block mechanical characteristic test includes compressive strength, water absorption, and paving block shock resistance. This research is done at the designed age 7, 14, 21, and 28 of concrete. This result shows that the paving block with 5% of rice husk ash variation has compressive strength increased every designed paving block ages. Compressive strength test results are 32,85 Mpa, 37,92 Mpa, 39,55 Mpa, and 41,19 Mpa consecutively. Water absorption test resulted in an increased of paving block water absorption in every variation reach 6,77%, 7,32%,8,98%, 9,05%, and 9,30%. While for the shock resistance test did not increased with the adding of rice husk ash with the average blows are 4,33, 4,33, 4,33 and 4,67 blows every designed age until it caused the paving block cracked and broken.Key word: rice husk ash, paving block, compressive strength, water absorption, shock resistance.